Avian influenza overview May – August 2020. (30th September 2020) - ,; ,; Adlhoch, Cornelia; Fusaro, Alice; Kuiken, Thijs; Niqueux, Éric; Staubach, Christoph; Terregino, Calogero; Muñoz Guajardo, Irene; Baldinelli, Francesca
Abstract : Between 16 May and 15 August 2020, seven highly pathogenic avian influenza (HPAI) A(H5N8) virus outbreaks were reported in Europe in poultry, with one outbreak reported in Bulgaria(n=1) andsix in Hungary (n=6) and one low pathogenic avian influenza (LPAI) A(H5N3) virus outbreak was reported in poultry in Italy. All six outbreaks detected in Hungary were secondary outbreaks and seem to be the tail end of the HPAI A(H5N8) epidemic that wasobserved in poultry over the winter and spring in central Europe from December 2019 (n=334).Genetic analysis of the HPAI A(H5N8) viruses isolated during this reporting period from Bulgaria and Hungary did not identify any major changes compared tothe viruses collected in the respective countries during the first months of 2020. This suggests a persistence of the virus in the two countries rather than new introductions via infectedwild birds. HPAI A(H5N8) virus has been detected in poultry and wild birds in western Russia within the reporting period, and as of the middle of September also in Kazakhstan. The presence of HPAI virus in western Russiaand in north Kazakhstan, spatially associated with autumnmigration routes of wild waterbirds, is of concern due to the possible spread of the virus via wild birds migrating to the EU.It is highly recommended thatMember States take appropriate measures to promptly detect suspected cases of HPAI, including increasing biosecurity measures. According to past experiences (2005‐2006 and 2016‐2017 epidemic waves), the northern and eastern European areas might be at higher risk of virus introduction in the coming autumn‐winter seasonand should be the key regions where prompt response measures to early detect the virusshould be set up. One human case due to A(H9N2) avian influenza virus infection was reported during the reporting period.